ORGANIZING THE AUDIT SYSTEM IN UZBEKISTAN ON THE BASIS OF INFORMATION TECHNOLOGIES: PROBLEMS AND SOLUTIONS - Meliev Israel Ismailovich (American Journals, 2025)
This article is devoted to the problems of organizing audit activity in Uzbekistan on the basis of information technologies and directions for their elimination. Relevance and necessity of using information technologies, review of literature on the subject, analyzes conducted on the subject and its results, conclusions obtained on the basis of research results, and author's suggestions for improvement of this field are described. Also, in the article, the types of software used in international audit practice, the factors affecting the non-use of audit software in the audit process, the problems of using modern software in the audit process, the software the procedure for forming the auditor's opinion by introducing evidence, the opportunities that can be achieved as a result of the use of information technologies in the audit are described based on the author's opinions.
Keywords: Audit activities, information technology, audit software, audit review, audit evidence, auditor opinion, audit report, audit services, IT audit, financial reporting audit, audit automation, digitalization, auditor, audit organization, audit team, expert, international standards of audit, audit methods and practices.